Nurses' Experiences in Carrying Out Palliative Care in Independent Nursing Practice - Ayu Febriani; Nurul Huda; Aminatul Fitri (CV. Rayyan Dwi Bharata, 2024)
Palliative care is total care that is carried out actively, especially for patients suffering from chronic diseases. The aim of this research is to obtain an overview of nurses' experiences in providing palliative care in independent nursing practice. The method used is qualitative with a descriptive phenomenological method design. The population is nurses who carry out palliative care in independent nursing practice with a sample of 5 nurses selected using the snowball sampling technique. Data collection techniques are interviews, observation and documentation. This research produced 6 themes related to nurses' experiences in carrying out palliative care in independent nursing, including: (1) Sufficient knowledge, (2) impact of palliative care, (3) Nursing Intervention, (4) Barriers, (5) Problem solving, and (6) Hope. In providing palliative nursing care, nurses must have sufficient knowledge regarding palliative care in order to provide maximum nursing care. While providing palliative care, nurses carry out nursing interventions to improve the patient's quality of life. Providing maximum nursing care is the main hope for every nurse in providing palliative care.